2016
DOI: 10.1159/000444721
|View full text |Cite
|
Sign up to set email alerts
|

Serous Cystadenocarcinoma of the Pancreas: Clinical Features and Management of a Rare Tumor

Abstract: Background/Aims: The vast majority of serous cystic neoplasms of the pancreas are benign, and small, asymptomatic lesions, which are generally managed with observation. However, some of these tumors may attain a large size and occasionally metastasize. Methods: In this study, we present a 78-year-old man with serous cystadenocarcinoma of the pancreas with liver metastases treated by distal pancreatectomy and liver ablation, who went on to develop new liver metastases 5 years after the initial operation. We per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…There have been a limited number of reports of chemotherapy or radiotherapy for serous cystadenocarcinomas with uncertain results though could be considered in unresectable cases [14]. Yet, the unexpected result of the misjudged treatment that in long period received our patient raises the question of a possible therapeutic effect of the anti-VEGF multi-targeted receptor tyrosine kinase inhibitor (sunitinib) in this type of cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…There have been a limited number of reports of chemotherapy or radiotherapy for serous cystadenocarcinomas with uncertain results though could be considered in unresectable cases [14]. Yet, the unexpected result of the misjudged treatment that in long period received our patient raises the question of a possible therapeutic effect of the anti-VEGF multi-targeted receptor tyrosine kinase inhibitor (sunitinib) in this type of cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Microscopically, the cells are uniform, round to polygonal, and have clear or pale eosinophilic cytoplasm with well-defined borders. Special stains highlight the abundant intracytoplasmic glycogen and absence of stainable mucin [3,14]. It is noteworthy to mention that in a recent review, Reid et al reported an association of SCNs in resection specimens with other neoplasms of the uninvolved pancreas in 13%.…”
Section: Discussionmentioning
confidence: 99%
“…SCNs have different biological characteristics than MCNs. SCNs are generally benign, with only 1 to 3% malignant potential [3], and can be followed up [5]. Approximately 10% of SCNs are manifested as unilocular without septa, which are easily misdiagnosed as MCNs [13].…”
Section: Discussionmentioning
confidence: 99%
“…SCNs and MCNs have different biological behaviors. Relevant studies have reported that only 1 to 3% of SCNs have been transformed into serous cystadenocarcinomas [3]. To date, only 25–30 serous cystadenocarcinomas have been reported worldwide [4].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, serous cystadenoma (SCA) may have the potential to progress to serous cystadenocarcinoma (SCAC), a rare diagnosis first described in 1989 [ 2 ]. To date, 35 malignant pancreatic SCN cases (15 with distant metastases) have been reported worldwide [ 3 ]. A recent systematic review showed overall favorable outcome for SCAC with 77% (17/22) alive at a median follow-up of 2 years [ 4 ].…”
Section: Introductionmentioning
confidence: 99%